IN RETROSPECT - THE FIFTY YEARS OF THE ROLLING THUNDER OPERATION: THE US AIR ATTACKS AND THE DEFENSE OF NORTH VIETNAM 1965-1968 - de Araújo, Johny Santana (Revista de Historia Social y de las Mentalidades, 2024)
In 1965, President Lyndon Johnson sent the first US military contingents to South Vietnam and launched a major bombing campaign in North Vietnam called the Rolling Thunder. This article discusses the reaction of North Vietnam with its defensive system to attacks, using MiG-17 and MiG-21 airplanes, how it made the most of its skills and equipment and how it overcame adversity, its own limitations and immense North American airpower.
Keywords: Conflict in Southeast Asia; Air War; Cold War; North Vietnam